2013
DOI: 10.3109/02656736.2012.753163
|View full text |Cite
|
Sign up to set email alerts
|

Common gene expression patterns responsive to mild temperature hyperthermia in normal human fibroblastic cells

Abstract: Common genes that were differentially expressed and/or acted within a gene network in response to MHT in NHF cells were identified. These findings provide the molecular basis for a further understanding of the mechanisms of the MHT response in NHF cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 50 publications
3
11
0
1
Order By: Relevance
“…By contrast, several genes that were upregulated or downregulated by ≥1.5-fold were identified in both cancer cell lines following exposure to MHT. These results were comparable to those from previous studies on MHT conditions using cancer or normal cell lines (17,(23)(24)(25)(26)(27). Previous studies have indicated that heat induces a significant decrease in mRNA and protein synthesis in order to increase the transcription of heat-responsive genes, such as HSPs, and that this overall reprogramming of gene expression permits the selective synthesis of HSPs (31,32).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…By contrast, several genes that were upregulated or downregulated by ≥1.5-fold were identified in both cancer cell lines following exposure to MHT. These results were comparable to those from previous studies on MHT conditions using cancer or normal cell lines (17,(23)(24)(25)(26)(27). Previous studies have indicated that heat induces a significant decrease in mRNA and protein synthesis in order to increase the transcription of heat-responsive genes, such as HSPs, and that this overall reprogramming of gene expression permits the selective synthesis of HSPs (31,32).…”
Section: Discussionsupporting
confidence: 89%
“…That is, cancer cells exposed to temperatures >42.5˚C undergo cell death; however, the exposure of cells to a temperature of up to 42.5˚C induces little or no cytotoxicity (2). In the present study, the exposure of HeLa and HSC-3 human SCC cells to MHT at 41˚C, below the inflection point, did not affect cell viability or the cell cycle, as has also been shown in our previous studies (24)(25)(26)(27). By contrast, several genes that were upregulated or downregulated by ≥1.5-fold were identified in both cancer cell lines following exposure to MHT.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In mammalian cells, heat activates the transcription of heat responsive genes, including HSPs, coincident with a bulk decrease in mRNA and protein syntheses, and this overall reprogramming of gene expression permits the selective synthesis of HSPs (40)(41)(42). In our previous studies using global-scale microarrays, we also detected a number of genes that were downregulated and participated in biological functions, including post-transcriptional modification and gene expression (43)(44)(45). This bulk decrease has been considered to represent a form of transcriptional suppression due to the binding of activated HSF1 to the promoter region of the gene (40).…”
Section: Function Of Hsf1mentioning
confidence: 99%